{[-2^5÷2^2-81÷3^2]÷(3-20)-2^6÷(-4)^2}×3^2=
Răspunsuri la întrebare
Răspuns de
1
{[-2^5÷2^2-81÷3^2]÷(3-20)-2^6÷(-4)^2}×3^2=
={[-2^3-3^4÷3^2]÷(-17)-2^6÷2^4}×3^2=
={[-8-3^2]÷(-17)-2^2}×3^2=
=[(-8-9)÷(-17)-2^2]×3^2=
=[(-17)÷(-17)-2^2]×3^2=
=(1-2^2)×3^2=
=(1-4)×3^2=
=(-3)×3^2=
=-3^3=-27
={[-2^3-3^4÷3^2]÷(-17)-2^6÷2^4}×3^2=
={[-8-3^2]÷(-17)-2^2}×3^2=
=[(-8-9)÷(-17)-2^2]×3^2=
=[(-17)÷(-17)-2^2]×3^2=
=(1-2^2)×3^2=
=(1-4)×3^2=
=(-3)×3^2=
=-3^3=-27
Alte întrebări interesante
Engleza,
8 ani în urmă
Biologie,
8 ani în urmă
Studii sociale,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă